Assessment of the blocking effect in classical conditioning of preferences (2011)
This experimental research was aimed to test Kamin's blocking effect in classical conditioning of preferences applied in the advertisement area. This study was divided into three parts: preliminary Study, Experiment 1, and Experiment 2. In the preliminary Study, both conditioned (a false publicity brand) and unconditioned stimuli (female figure with a controlled waist-to-hip ratio) were selected. Experiments 1 and 2 consisted of training in classical conditioning of preferences and blocking effect. 17-25 year-old undergraduate students of different careers participated in the present study. According to the results, a blocking effect was observed, suggesting an explanation for different phenomena in fields such as marketing or advertisement, especially when implying brands competition.